2021
DOI: 10.3389/fmars.2021.665576
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Lipid Effects on Gut Microbiota of First Feeding Atlantic Salmon (Salmo salar L.)

Abstract: Decline in fish oil and fish meal availability has forced the aquaculture sector to investigate alternative and sustainable aquafeed ingredients. Despite that several studies have evaluated the effect of fish oil replacement in aquaculture fish species, there is a knowledge gap on the effects of alternative dietary lipid sources on the gut microbiota in early life stages of Salmo salar. The present study evaluated the influence of dietary administration of two different lipid sources (fish oil and vegetable oi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…Similar results can also be found in largemouth bass (Micropterus salmoides) using algae meal [107] or Nile tilapia (Oreochromis niloticus) using rice protein concentrate [108]. However, in salmon, a complete FO substitution did not alter the intestinal bacterial population using a mix of rapeseed, linseed, and palm oils [109]. In Nile tilapia, algae oil inclusion does not affect alpha microbiome diversity either [110].…”
Section: Discussionsupporting
confidence: 52%
“…Similar results can also be found in largemouth bass (Micropterus salmoides) using algae meal [107] or Nile tilapia (Oreochromis niloticus) using rice protein concentrate [108]. However, in salmon, a complete FO substitution did not alter the intestinal bacterial population using a mix of rapeseed, linseed, and palm oils [109]. In Nile tilapia, algae oil inclusion does not affect alpha microbiome diversity either [110].…”
Section: Discussionsupporting
confidence: 52%
“…Under current conditions, the gut microbial community composition was very conserved, with only an increase in the relative abundance of Chloroflexi in the PI of fish fed the SPICY 0.1% diet. This is a widespread and metabolically diverse phylum of bacteria that has been reported as part of fish microbiota ( 44 , 100 , 101 ), but whose role remains unknown. No differences were found in the values of the F/B ratio, which is a well-documented factor whose changes have been used as a biomarker of intestinal dysbiosis in fishes ( 102 ).…”
Section: Discussionmentioning
confidence: 99%
“…The assembly of intestinal microbiota into distinct communities are important during the development of fish larvae ( 75 ). It is well demonstrated that dietary nutritional composition can affect the intestinal microbiota composition and diversity in fish species ( 28 , 76 , 77 ). In the present study, dietary phospholipids supplementation produced no significant difference in the intestinal microbial community composition at the phyla level, and the Proteobacteria, Firmicutes, and Actinomycetes were the dominant phyla in both the two extreme treatments with the supplementation of phospholipids (PL8) or not (PL0, control), in accordance with previous studies reviewed by Borges etal.…”
Section: Discussionmentioning
confidence: 99%